Queen of Heartbreak Trail. - Brackbill, Eleanor Phillips (TwoDot, 2016)
The story of Harriet Smith Pullen's early life, from her childhood journeys by covered wagon to her family's subsistence in sod houses on the Dakota prairie where they survived grasshopper plagues, floods, fires, blizzards, and droughts is a narrative of American migration and adventure that still resonates today. But there is much more to the legendary woman's life, revealed here for the first time by Eleanor Phillips Brackbill, her great-granddaughter, who has traveled the path of her ancestor, delving into unpublished material, as well as sharing family stories in this American story that will capture the imagination of a new generation. After migrating by emigrant train to Washington Territory, Harriet endured typhoid fever and a shipwreck, then homesteaded among the Quileute people on the coast of Washington, where she married Dan Pullen, with whom she was an equal partner in ranching and managing an Indian fur-trading post before a life-changing series of events caused her to strike out for the north. In 1897, she landed in Skagway, Alaska, broke and alone after leaving her husband and four children in Washington, determined to make a fresh start and to reunite with her sons and daughter. Newly independent and empowered, she became an entrepreneur, single-handedly hauling prospectors' provisions into the mountains where gold beckoned and then starting the Pullen House, an acclaimed hotel. Later in life, Harriet would entertain her guests with fabulous stories about the gold rush and her renowned collection of Alaskan Native artifacts and gold rush relics. She achieved near-legendary status in Alaska during her lifetime and The Queen of Heartbreak Trail brings to life moments that are well known and moments that have never before been published?her arrest for holding a claim jumper at gunpoint, her grueling courtroom testimony defending herself against the spurious accusations of a malevolent employer, and, how, in her father's words, she "turned out" her husband of twenty years.